2022
DOI: 10.3390/cells11040694
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of an Inducible Cx43 Overexpression System in Mouse Embryonic Stem Cells

Abstract: Connexins (Cx) are a large family of membrane proteins that can form intercellular connections, so-called gap junctions between adjacent cells. Cx43 is widely expressed in mammals and has a variety of different functions, such as the propagation of electrical conduction in the cardiac ventricle. Despite Cx43 knockout models, many questions regarding the biology of Cx43 in health and disease remain unanswered. Herein we report the establishment of a Cre-inducible Cx43 overexpression system in murine embryonic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…This discrepancy is explained later herein. Cx43 is mainly located in the cytoplasm and barely expressed in areas connecting non-adjacent cells on the cell membrane [148]. In HCC, studies have shown that Cx43 expression is associated with the presence of histological differentiation, multiple foci, vascular tumor thrombosis, and early recurrence [149].…”
Section: Connexin 43 (Cx43)mentioning
confidence: 99%
“…This discrepancy is explained later herein. Cx43 is mainly located in the cytoplasm and barely expressed in areas connecting non-adjacent cells on the cell membrane [148]. In HCC, studies have shown that Cx43 expression is associated with the presence of histological differentiation, multiple foci, vascular tumor thrombosis, and early recurrence [149].…”
Section: Connexin 43 (Cx43)mentioning
confidence: 99%
“…Among the 21 connexin isomers identified in the human genome, Connexin43 (Cx43) is the most widely expressed and critical connexin. It plays an essential role in regulating GJs function, controlling cell migration and proliferation, wound repair, and immune regulation (Turovsky et al, 2021;Niemann et al, 2022). In 2013, Kato et al first demonstrated the existence of functional GJs in hPDLCs (Kato et al, 2013).…”
Section: Introductionmentioning
confidence: 99%